Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00392-006-0466-8
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of successful cardioversion of atrial fibrillation in patients with organic heart disease

Abstract: The aim of the study was to evaluate the prognostic impact of successful cardioversion (CV) compared to failed CV in patients with atrial fibrillation (AF) and organic heart disease. A total of 471 consecutive patients with organic heart disease from the prospective single center anticoagulation registry ANTIK who underwent CV of AF or atrial flutter were analyzed. 417 patients (89%) could be successfully cardioverted. In 54 patients (11%) CV failed, these patients remained in AF. After 5 years there were 92 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While prospective studies have not demonstrated differences in mortality between rate control and rhythm control strategies, sinus rhythm may provide significant symptomatic improvement, and many patients with persistent atrial fibrillation undergo electrical or pharmacological cardioversion [2,3,4,5]. Direct current cardioversion (DCCV) is associated with known risks including thromboembolism, complications associated with sedation such as aspiration or respiratory arrest, sinus bradycardia, hypotension and rarely pulmonary edema [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…While prospective studies have not demonstrated differences in mortality between rate control and rhythm control strategies, sinus rhythm may provide significant symptomatic improvement, and many patients with persistent atrial fibrillation undergo electrical or pharmacological cardioversion [2,3,4,5]. Direct current cardioversion (DCCV) is associated with known risks including thromboembolism, complications associated with sedation such as aspiration or respiratory arrest, sinus bradycardia, hypotension and rarely pulmonary edema [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…DCCVs are associated with risks including thromboembolism, complications associated with sedation/anesthesia (e.g. aspiration or respiratory arrest), sinus bradycardia, hypotension and, rarely, pulmonary edema [10,11,12,13]. There are also reports of acute rabdomyolysis and acute renal failure after cardioversion in seriously ill patients including those with cardiopulmonary arrest [14,15,16].…”
mentioning
confidence: 99%